AMP‐activated protein kinase regulates nicotinamide phosphoribosyl transferase expression in skeletal muscle. (13th September 2013) - Brandauer, Josef; Vienberg, Sara G.; Andersen, Marianne A.; Ringholm, Stine; Risis, Steve; Larsen, Per S.; Kristensen, Jonas M.; Frøsig, Christian; Leick, Lotte; Fentz, Joachim; Jørgensen, Sebastian; Kiens, Bente; et al.
Key points:   NAD is a substrate for sirtuins (SIRTs), which regulate gene transcription in response to specific metabolic stresses.   Nicotinamide phosphoribosyl transferase (Nampt) is the rate‐limiting enzyme in the NAD salvage pathway.   Using transgenic mouse models, we tested the hypothesis that skeletal muscle Nampt protein abundance would increase in response to metabolic stress in a manner dependent on the cellular nucleotide sensor, AMP‐activated protein kinase (AMPK).   Exercise training, as well as repeated pharmacological activation of AMPK by 5‐amino‐1‐β‐d ‐ribofuranosyl‐imidazole‐4‐carboxamide (AICAR), increased Nampt protein abundance. However, only the AICAR‐mediated increase in Nampt protein abundance was dependent on AMPK.   Our results suggest that cellular energy charge and nutrient sensing by SIRTs may be mechanistically related, and that Nampt may play a key role for cellular adaptation to metabolic stress. Abstract  Deacetylases such as sirtuins (SIRTs) convert NAD to nicotinamide (NAM). Nicotinamide phosphoribosyl transferase (Nampt) is the rate‐limiting enzyme in the NAD salvage pathway responsible for converting NAM to NAD to maintain cellular redox state. Activation of AMP‐activated protein kinase (AMPK) increases SIRT activity by elevating NAD levels. As NAM directly inhibits SIRTs, increased Nampt activation or expression could be a metabolic stress response. Evidence suggests that AMPK regulates Nampt mRNA content, but whether repeated AMPK activation is necessary for increasing Nampt protein levels is unknown. To this end, we assessed whether exercise training‐ or 5‐amino‐1‐β‐d ‐ribofuranosyl‐imidazole‐4‐carboxamide (AICAR)‐mediated increases in skeletal muscle Nampt abundance are AMPK dependent. One‐legged knee‐extensor exercise training in humans increased Nampt protein by 16% ( P < 0.05) in the trained, but not the untrained leg. Moreover, increases in Nampt mRNA following acute exercise or AICAR treatment ( P < 0.05 for both) were maintained in mouse skeletal muscle lacking a functional AMPK α2 subunit. Nampt protein was reduced in skeletal muscle of sedentary AMPK α2 kinase dead (KD), but 6.5 weeks of endurance exercise training increased skeletal muscle Nampt protein to a similar extent in both wild‐type (WT) (24%) and AMPK α2 KD (18%) mice. In contrast, 4 weeks of daily AICAR treatment increased Nampt protein in skeletal muscle in WT mice (27%), but this effect did not occur in AMPK α2 KD mice. In conclusion, functional α2‐containing AMPK heterotrimers are required for elevation of skeletal muscle Nampt protein, but not mRNA induction. These findings suggest AMPK plays a post‐translational role in the regulation of skeletal muscle Nampt protein abundance, and further indicate that the regulation of cellular energy charge and nutrient sensing is mechanistically related.